Analysis of students' misconceptions on the material of life organization systems - Hasna' Nur Aulia; Kurnia Ningsih; Titin Titin (JPBIO (Jurnal Pendidikan Biologi), 2021)
This study aims to analyze students' misconceptions on the material of life organization systems and to determine the factors that cause misconceptions in students at SMP Negeri 10 Pontianak. The research subjects were 30 students of class VIII H. The method used was case study method. Data collection techniques used diagnostic tests with CRI and non-tests in the form of questionnaires and interviews. The results showed that there were students' misconceptions on the material of life organization systems. The percentage of students' misconceptions that fall into the high category is the sub-material on the organism (73.33%). In the medium category, there are sub material organizations of life (56.67%), cells (60.83%), and organs (65.83%). In the low category, there are sub-material tissues (36.67%) and organ systems (27.5%). There are 5 factors that cause misconceptions, namely associative thinking (64.2%), incomplete reasoning (66.1%), wrong intuition (62.1%), student ability (57.1%), and student interest (54.3%).